Metabolic, Cardiac, and Renal Effects of the Slow Hydrogen Sulfide-Releasing Molecule GYY4137 During Resuscitated Septic Shock in Swine with Pre-Existing Coronary Artery Disease. Issue 2 (August 2017) - Nußbaum, Benedikt L.; Vogt, Josef; Wachter, Ulrich; McCook, Oscar; Wepler, Martin; Matallo, José; Calzia, Enrico; Gröger, Michael; Georgieff, Michael; Wood, Mark E.; Whiteman, Matthew; Radermacher, Peter; et al.
Abstract : ABSTRACT: Decreased levels of endogenous hydrogen sulfide (H2 S) contribute to atherosclerosis, whereas equivocal data are available on H2 S effects during sepsis. Moreover, H2 S improved glucose utilization in anaesthetized, ventilated, hypothermic mice, but normothermia and/or sepsis blunted this effect. The metabolic effects of H2 S in large animals are controversial. Therefore, we investigated the effects of the H2 S donor GYY4137 during resuscitated, fecal peritonitis-induced septic shock in swine with genetically and diet-induced coronary artery disease (CAD). Twelve and 18 h after peritonitis induction, pigs received either GYY4137 (10 mg kg −1, n = 9) or vehicle (n = 8). Before, at 12 and 24 h of sepsis, we assessed left ventricular (pressure-conductance catheters) and renal (creatinine clearance, blood NGAL levels) function. Endogenous glucose production and glucose oxidation were derived from the plasma glucose isotope and the expiratory 13 CO2 / 12 CO2 enrichment during continuous i.v. 1, 2, 3, 4, 5, 6- 13 C6 -glucose infusion. GYY4137 significantly increased aerobic glucose oxidation, which coincided with higher requirements of exogenous glucose to maintain normoglycemia, as well as significantly lower arterial pH and decreased base excess. Apart from significantly lower cardiac eNOS expression and higher troponin levels, GYY4137 did not significantly influence cardiac and kidney function or the systemic inflammatory response. During resuscitated septic shock in swine with CAD, GYY4137 shifted metabolism to preferential carbohydrate utilization. Increased troponin levels are possibly due to reduced local NO availability. Cautious dosing, the timing of GYY4137 administration, and interspecies differences most likely account for the absence of any previously described anti-inflammatory or organ-protective effects of GYY4137 in this model. Abstract : Supplemental Digital Content is available in the text